2020
DOI: 10.1167/tvst.9.9.16
|View full text |Cite
|
Sign up to set email alerts
|

Auto-Processed Retinal Vessel Shadow View Images From Bedside Optical Coherence Tomography to Evaluate Plus Disease in Retinopathy of Prematurity

Abstract: To describe the creation of en face retinal vessel shadow view (RVSV) optical coherence tomography (OCT) images and assess the feasibility of using these for evaluating vascular disease in preterm infants at risk for retinopathy of prematurity (ROP). Methods: In this exploratory study, we selected images from eyes with a range of ROP vascular disease, prospectively acquired from preterm infants using an investigational, noncontact, handheld, bedside swept-source OCT. We autosegmented OCT volumes using custom i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…As stated in that study, the primary goal of imaging was the macula, which limited capture of the arcades. Since then, we have modified OCT speed, the imaging protocol, and image processing with the goal of acquiring scans that provide sufficient information for the diagnosis of plus disease . The visualization reported here, by providing integrated data on the relative location of abnormalities of retinal tissue, retinal vasculature, and extraretinal neovascularization, improves researchers’ understanding of pathology based on OCT morphology and reveals indicators and associations that may be helpful in categorizing plus disease …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated in that study, the primary goal of imaging was the macula, which limited capture of the arcades. Since then, we have modified OCT speed, the imaging protocol, and image processing with the goal of acquiring scans that provide sufficient information for the diagnosis of plus disease . The visualization reported here, by providing integrated data on the relative location of abnormalities of retinal tissue, retinal vasculature, and extraretinal neovascularization, improves researchers’ understanding of pathology based on OCT morphology and reveals indicators and associations that may be helpful in categorizing plus disease …”
Section: Discussionmentioning
confidence: 99%
“…For 3-D visualization, we incorporated en face OCT images extracted from a narrow axial window bracketed around the retinal pigment epithelium (retinal vessel shadow view [RVSV-OCT]) and thickness maps generated using software optimized for automatic segmentation (DOCTRAP version 66.2). We extracted the internal limiting membrane and Bruch membrane segmentation from OCT volumes.…”
Section: Methodsmentioning
confidence: 99%
“…To monitor these stress events, we relied on preset alarms for each infant, as opposed to clinically defined bradycardia (<80 bpm), tachycardia (>200 bpm), and oxygen desaturation (<80%) . While OCT images have not been shown to be equivalent to BIO for ROP determination, this has been the focus of multiple studies demonstrating the future potential . Reduction in early-life stress might be possible in the future if OCT imaging proved comparable with BIO for screening.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these are not visible using BIO. We and other researchers have developed faster investigational OCT systems to image moving eyes of awake infants in the ICN and to evaluate vascular disease in eyes with ROP . Bedside noncontact, infrared OCT imaging does not use bright visible light and does not require pupil dilation, although the latter facilitates peripheral retinal imaging .…”
Section: Introductionmentioning
confidence: 99%
“…One novel method described included extracting two-dimensional en face retinal vascular shadow view (RVSV) montage images from structural OCT scans, which can optimize visualization of the posterior pole vasculature by eliminating potentially distracting choroidal vasculature. RVSV-OCT images present with more distinct retinal vessels, better retinal vessel contrast and crisper margins than conventional ones, and thus, are gradable for plus, pre-plus or no plus disease [ 47 , 48 ]. Fourth, several studies showed that OCT was able to image a treatment response, such as regression of macular edema following laser or intravitreal anti-VEGF injection [ 49 , 50 ].…”
Section: Oct and Octa In Retinal Vascular Diseasesmentioning
confidence: 99%